Gap junctions in cells of the immune system: structure, regulation and possible functional roles - Sáez,J.C. (2000)
Gap junction channels are sites of cytoplasmic communication between contacting cells. In vertebrates, they consist of protein subunits denoted connexins (Cxs) which are encoded by a gene family. According to their Cx composition, gap junction channels show different gating and permeability properties that define which ions and small molecules permeate them. Differences in Cx primary sequences suggest that channels composed of different Cxs are regulated differentially by intracellular pathways under specific physiological conditions. Functional roles of gap junction channels could be defined by the relative importance of permeant substances, resulting in coordination of electrical and/or metabolic cellular responses. Cells of the native and specific immune systems establish transient homo- and heterocellular contacts at various steps of the immune response. Morphological and functional studies reported during the last three decades have revealed that many intercellular contacts between cells in the immune response present gap junctions or "gap junction-like" structures. Partial characterization of the molecular composition of some of these plasma membrane structures and regulatory mechanisms that control them have been published recently. Studies designed to elucidate their physiological roles suggest that they might permit coordination of cellular events which favor the effective and timely response of the immune system.